Evaluation of the Efficacy of an Insecticidal Paint Based on Chlorpyrifos and Pyriproxyfen in a Microencapsulated Formulation Against Rhynchophorus ferrugineus (Coleoptera: Curculionidae) - Llácer, Elena; Dembilio, Óscar; Jaques, Josep A. (2017)
The weevil Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) is an important pest of palms. It has recently colonized the Mediterranean Basin where it is a serious problem on ornamental Phoenix canariensis (hort. ex Chabaud) palms. The efficacy of an insecticidal paint based on chlorpyrifos and pyriproxyfen in a microencapsulated formulation (Inesfly IGR FITO, Industrias Quimicas Inesba S.L., Paiporta, Spain) against this weevil has been studied. Laboratory results proved that pyriproxyfen has no effect against R. ferrugineus when applied in this microencapsulated formulation. Semifield trials dismissed Inesfly IGR FITO as a curative insecticide but showed the potential of this product in the preventative control of R. ferrugineus in palms. One single application could prevent infestation for up to 6 mo with a mean efficacy of 83.3%.